2016
DOI: 10.1136/heartjnl-2016-309890.132
|View full text |Cite
|
Sign up to set email alerts
|

132 Diagnostic Accuracy of Stress Echocardiography Compared with Invasive Coronary Angiography with Fractional Flow Reserve for The Diagnosis of Haemodynamically Significant Cad in Patients with Known or Suspected CAD

Abstract: unknown. We hypothesised that information of ischemia and atherosclerosis which can be achieved simultaneously by ultrasound (SE and carotid ultrasound) can provide incremental prognostic information in these patients. Methods Consecutive patients with no previous history of CAD investigated with SE for suspected angina underwent a simultaneous carotid ultrasound. Carotid plaque burden was assessed. Patients were followed up for combined major adverse cardiac events (MACE) of all-cause mortality, non-fatal myo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Estimates from different patient groups were sometimes used to populate the model. For example, in model 1, the diagnostic accuracy of stress ECHO was derived from a study diagnosing significant coronary artery disease, rather than PPCI patients 31. Despite these potential limitations, our model represents the best available evidence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Estimates from different patient groups were sometimes used to populate the model. For example, in model 1, the diagnostic accuracy of stress ECHO was derived from a study diagnosing significant coronary artery disease, rather than PPCI patients 31. Despite these potential limitations, our model represents the best available evidence.…”
Section: Discussionmentioning
confidence: 99%
“…The assumption of 100% sensitivity and specificity for CMR and FFR results in identical probabilities and outcomes, but differences in costs for the two arms. Sensitivity and specificity values for stress ECHO were obtained from Gurunathan et al 31…”
Section: Methodsmentioning
confidence: 99%
“…For example, in the model for patients with multivessel disease, the diagnostic accuracy of stress ECHO (its sensitivity and specificity) was taken from a paper considering the diagnosis of significant coronary artery disease, rather than a PPCI population, and estimates are based on the number of vessels rather than the number of patients. 39 In the base-case analyses for multivessel disease, CMR and pressure wire were treated as reference standards, and both were assumed to have 100% sensitivity and specificity. There are suggestions in the literature that this is reasonable; for example, Emrich et al 103 found that CMR correctly identified all 20 out of 125 patients with MI in their study.…”
Section: Economic Evaluationmentioning
confidence: 99%
“…The accuracy of stress echo tests for the detection of coronary artery disease is expressed as the sensitivity and specificity of the technique for the detection of angiographically demonstrated stenosis. Nonetheless, this parameter has a number of limitations, some reflecting the limitations of an angiographic cutoff for significant disease, including the variation of the physiologic effect of a stenosis based on site, length, and vessel size, as well as over-and under-estimation of coronary lesion severity [4].…”
Section: Introductionmentioning
confidence: 99%